Consumer Responses to the Development of Tourism Destinations through Molecular Gastronomy: An Analysis of Interest and Contributing Factors - Sufianti, R. Arti; Maulina, Lien; Saepudin, Deden; Utomo, Bambang Sapto (Side: Scientific Development Journal, 2025)
The development of tourism destinations through unique culinary experiences has become a key strategy in attracting tourists and boosting the tourism industry. Among these innovations, molecular gastronomy stands out as an emerging trend that blends science and cuisine to create novel and interactive dining experiences. This study aims to explore consumer responses to the development of tourism destinations through molecular gastronomy, with a particular focus on understanding the factors that drive interest and participation in such gastronomic experiences. Through a comprehensive analysis, this research examines consumer perceptions and preferences regarding molecular gastronomy as a potential attraction at tourist destinations. The study identifies key aspects that influence consumer interest, such as the novelty of the gastronomic experience, the perceived value of the experience, and the role of promotional efforts in enhancing awareness and attracting visitors. Additionally, the research highlights the importance of affordable pricing and high-quality tastes as critical factors in shaping consumer willingness to visit destinations offering molecular gastronomy experiences. Furthermore, the study delves into the expectations of consumers regarding the involvement of governmental and tourism authorities in promoting molecular gastronomy-based products to enhance the appeal of tourist destinations. It explores the desire for further development of these gastronomic offerings as part of broader tourism strategies aimed at diversifying the types of attractions available to travelers. Overall, the findings suggest that molecular gastronomy has significant potential to become a major culinary attraction in tourism, with consumer responses indicating a high level of interest in experiencing such innovations. The study provides valuable insights into the role of culinary experiences in tourism development and underscores the importance of targeted marketing strategies, quality control, and government support in fostering the growth of this unique tourism sector.